Symptomatic cycling Cushing disease managed by simultaneous bilateral laparoscopic adrenalectomy in a 11-year-old boy - Khalid M Al-Otaibi; Mohammad A Abduljabbar (Wolters Kluwer Medknow Publications, 2014)
We report symptomatic cycling Cushing disease in a 11-year-old boy that was managed with simultaneous bilateral laparoscopic adrenalectomy. Positioning and the surgical technique have been fully described. Excellent results were achieved. Recent application of laparoscopic adrenalectomy for various adrenal pathology is highly effective and offers better results than open surgery. Post-operative recovery after laparoscopic technique is significantly shorter than the open technique.